Applications of Internet of Things, Remote Sensing, and AI for Precision Agriculture and its Adoption Status in Nepal - Aarju Aryal; Yogesh Sapkota; Bishal Lamichhane; Jiban Shrestha (Green Engineering Society, 2026)
Modern technologies combined with precision agriculture have made revolutionary advances in the field of agriculture. The Internet of Things (IoT), remote sensing, wireless sensor networks, machine learning, and smart farm management systems have brought agriculture into a new era. In this context, the purpose of this review is to summarize the most recent advanced tools and their potential directions for further research by synthesizing the recent literature. Sensors, robotics, global positioning systems (GPS), satellites, and aerial imaging drones have facilitated data-driven actions, programmed management, and real-time monitoring in agricultural systems. These tools, when combined with Artificial Intelligence (AI) and machine learning, enable real-time decision-making and smart farm management. Some advanced applications include computer-based image recognition in weed control robots, early pest and disease detection through image identification, irrigation based on field water, fertilizer application through soil nutrient mapping, livestock health tracking through behavioral biometrics, and yield prediction analytics to inform breeding and harvest planning. The emergence of